Extreme cinema : affective strategies in transnational media - Kerner, Aaron; Knapp, Jonathan L. (Edinburgh University Press, 2016)
Examines how extreme cinema mobilises explicit content and highly embellished aesthetics to affect spectators. Extreme Cinema examines the highly stylized treatment of sex and violence in post-millennial transnational cinema, where the governing convention is not the narrative but the spectacle. Using profound experiments in form and composition, including jarring editing, extreme close-ups, visual disorientation and sounds that straddle the boundary between non-diegetic and diegetic registers, this mode of cinema dwells instead on the exhibition of intense violence and an acute intimacy with the sexual body. Interrogating works such as Wetlands and A Serbian Film, as well as the sub-culture of YouTube 'reaction videos', Aaron Michael Kerner and Jonathan L. Knapp demonstrate the way content and form combine in extreme cinema to affectively manipulate the viewing body. Key features. Considers a wide scope of international approaches to extreme cinema Draws together a diverse body of theoretical ideas to work towards a conceptualisation of the affective potential in the cinema Engages critically with films that have received little scholarly attention Cases studies include Wetlands, A Serbian Film and Helter Skelter